2004
DOI: 10.1158/0008-5472.can-03-3393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Serum Estrogens in Postmenopausal Women

Abstract: Elevated circulating estrogens and a sedentary lifestyle increase risk for breast cancer. The effect of exercise on circulating estrogens in sedentary postmenopausal women is unknown. The objective of this study was to examine the effects of a 12-month moderate-intensity exercise intervention on serum estrogens. We randomly assigned 173 sedentary, overweight (body mass index > 24.0 kg/m 2 , body fat > 33%), postmenopausal women, ages 50 -75 years, not using hormone therapy, living in the Seattle, Washington, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
1
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(293 citation statements)
references
References 23 publications
13
268
1
11
Order By: Relevance
“…The hypothesized mechanism of physical activity influencing mammographic density via sex hormone changes applies especially to obese postmenopausal women, who have higher levels of sex hormone concentrations than leaner postmenopausal women, due to the formation of estrogens in fatty tissue (10,21,22). Thus, higher levels of physical activity may be associated with decreased mammographic density levels among obese postmenopausal women by decreasing sex hormone concentrations directly or indirectly by reducing body fat (7). In a recently published yearlong randomized controlled trial, exercise had a favorable effect on decreasing circulating sex hormone concentrations among overweight postmenopausal women (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesized mechanism of physical activity influencing mammographic density via sex hormone changes applies especially to obese postmenopausal women, who have higher levels of sex hormone concentrations than leaner postmenopausal women, due to the formation of estrogens in fatty tissue (10,21,22). Thus, higher levels of physical activity may be associated with decreased mammographic density levels among obese postmenopausal women by decreasing sex hormone concentrations directly or indirectly by reducing body fat (7). In a recently published yearlong randomized controlled trial, exercise had a favorable effect on decreasing circulating sex hormone concentrations among overweight postmenopausal women (7).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have examined the relationship between physical activity and mammographic density (5,6). Physical activity may influence mammographic density by favorably changing certain hormones associated with mammographic density and breast cancer risk (7). Demonstration of beneficial changes in mammographic density associated with increased physical activity could be used to motivate women to be more physically active.…”
Section: Introductionmentioning
confidence: 99%
“…The reversal direction, for instance, is supported by studies showing a decrease in testosterone levels after weight and body fat loss in overweight women. 79,80 Furthermore, adipose tissue, with its 17b-hydroxysteroid dehydrogenase activity, has been suggested to be an important site of peripheral testosterone production. 81,82 On the other hand, testosterone treatment has been associated with changes in body composition, including a redistribution of fat depots.…”
Section: Cardiovascular Risk Factors and Diseasementioning
confidence: 99%
“…The effect of physical activity on sex hormones may vary according to hormone receptor status (Sieri et al 2009), across the menopausal transition (Schmitz et al 2007), and also with body fat (McTiernan et al 2004a;McTiernan et al 2004b). Three RCTs have examined the effect of exercise on sex hormone levels and weight change in postmenopausal women.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Three RCTs have examined the effect of exercise on sex hormone levels and weight change in postmenopausal women. In the PATH trial, women assigned to the exercise group who lost more than 2% body fat experienced significantly lower blood estrogen and androgen levels relative to controls after 12 months of exercise (McTiernan et al 2004a;McTiernan et al 2004b). Likewise, the SHAPE trial showed that relative to controls, androgen (but not estrogen) levels decreased significantly in exercisers who lost >2% body fat after 4 months of exercise (Monninkhof et al 2009).…”
Section: Sex Hormonesmentioning
confidence: 99%